Understanding UV-vis spectra of halogenated tetraazaperopyrenes (TAPPs): a computational study - Höfener, Sebastian; Günther, Benjamin; Gade, Lutz H. (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2019)
The UV-vis absorption and emission spectra of halogenated tetraazaperopyrenes (TAPPs) have been investigated employing second-order approximate coupled cluster (CC2) and (time-dependent) density functional theory (DFT). We have found that the qualitative estimates of (vertical) absorption and excitation energies are possible within a single particle picture based on frontier orbitals, but the single particle picture is not sufficient to achieve quantitative accuracy. Going from the single-particle picture to the many-particle picture improves the agreement with experimental results, but still no satisfying correlation of theory and experiment is obtained. The comparison of CC2- and DFT-based methods reveals that deviations from the experimental results cannot be explained by deficiencies of the electronic-structure methods but rather stem from neglecting vibrational effects. An agreement of theoretical results and experimental spectra is found for adiabatic excitation energies, which are given as energy differences of vibronic states, which are directly accessible using both theoretical and experimental methods. The most pronounced vibronic influence is found for the Stokes shifts, which are significantly overestimated by computing the vertical electronic transitions only. Based on the vibronic contributions, the small Stokes shift of the TAPP compounds can be explained by the temperature dependence of the vibrationally resolved UV–vis spectra.
Gesehen am 23.05.2019